Big data in purchasing and supply management: a research agenda. (28th January 2021) - Arvidsson, Ala Pazirandeh; Jonsson, Patrik; Kaipia, Riikka
This study aims to synthesise knowledge about big data (BD) in the area of purchasing and supply management (PSM) and to develop an agenda for future research. A systematic literature review approach was employed, and 65 articles were synthesised based on a classification for BD in PSM to identify research gaps and opportunities. Literature in this area is descriptive and conceptual in nature, and modelling methods are favoured. BD applications were identified for supplier selection, supply risk management, and supply visibility. Based on the complexity of access and use of BD, we identify a need for contextualised theory-building studies.